Manajemen Religious Culture Satlogi Santri Pondok Pesantren Zainul Hasan Genggong Probolinggo - Umi Haniah; Ismatul Izzah (LP3M Universitas Islam Zainul Hasan Genggong, 2020)
One of the goals of Islamic education is to form the personality of students who have mercy. Ahlak and one’s behavior is a reflection of the knowledge and knowledge that can be obtained, therefore with the development of time, science and technology it has become an obligation for educators and educators to always be able to apply the knowledge and knowledge that has been obtained in everyday life . Absolute education or character education, in practice is not easy to implement. Because one’s actions or actions are influenced by the mindset and the accompanying environment, therefore in the Zainul Hasan Islamic Boarding School educational institution Genggong Probolinggo in the learning process develops and manages how the religious culture of Satlogi Santri and 9 Budi Utama santri can always be formed in the character of students even though not the students or students who do not live in Islamic boarding schools.